“La oralidad en el desarrollo del lenguaje de los niños de 3 a 4 años” - Rea Tutin, Jessica Nataly (2022)
The current research was carried with the purpose to diagnose orality into language development from children 3 to 4 years old, Initial Education, specifically, Pujilí Educational Unit, located in the Pujilí canton, Cotopaxi Province, zone 3 and its impact about language development. The problem is generated by the information lack, who has the teacher about orality to be executed, correctly, into infant language development, as well as the confidence lack by children part has impeded the socialization process at demonstrating shyness, for participation within class. To perform this research, it was made a bibliographical review within the educational field by using the same qualitative approach, what allowed getting real information, from the direct interaction between the researcher and the study object, as well as, it was used the experimental and ethnographic methods, the same, which allowed to study the variables, at observing a social research phenomenon with the data collection techniques help and instruments, whose it made possible to collect information from different contexts. The general objective this research was to identify the children's oral language development, through the interview and the observation sheet application, to develop orality into children 3 to 4 years, from "Pujilí" Educational Unit, the research type was exploratory, it allows knowing, what activities use with the children, such as dynamics, orofacial exercises, imitation activities, repeating animal sounds, songs and tongue twisters, it worked with the 25 students, 10 boys, 15 girls and 1 teacher, at allowing case study, concluding, what the playful pedagogical strategies should be applied with greater emphasis according to the student' needs, this case should be determined activities, which help the communication and social relationships development, allowing the child to express their emotions and ideas, towards others.